Very Broad Metal Ion Beam Source for Ion Implantation and Coating Deposition Technologies; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Stepanov I. B. Igor Borisovich (Chemistry and Physics of Materials Surface, 2014)
Title screen